SISTEM PAKAR PENYAKIT PREEKLAMPSIA PADA IBU HAMIL DENGAN METODE FUZZY PADA KLINIK MULYA RAHAYU CURUG - Ahmad Fikri Zaki (CV. Multi Kreasi Media, 2023)
Pregnancy is a phase where the body of a pregnant woman will experience very significant changes both in terms of body shape and emotional experience. At the Mulya Rahayu Curug Clinic located at JLRaya PLP Curug, No. 124, Serdang Wetan, Curug, Jl. Raya PLP Curug, Serdang Wetan, Tangerang, Tangerang Regency is engaged in Health, especially for pregnant women. Where in the clinic is still done manually. When a pregnant woman wants to have a consultation related to preeclampsia with a doctor, it can only be done on a certain schedule and pregnant women have to wait for the doctor to come and it cannot be done only outside of practice hours. And that makes it difficult for pregnant women to prove to a doctor about preeclampsia. provide solutions and advice for more knowledge for pregnant women and clinic staff in order to help pregnant women with problems, especially preeclampsia. The method used is observation, interview and literature study and the development method is the fuzzy method. The results of this study are expected to help pregnant women and health workers in obtaining information related to preeclampsia.